Acute yellow oleander (Thevetia peruviana) poisoning: cardiac arrhythmias, electrolyte disturbances, and serum cardiac glycoside concentrations on presentation to hospital - Eddleston, M.; Ariaratnam, A.C.; Sjöström, L.; Jayalath, S.; Rajakanthan, K.; Rajapakse, S.; Colbert, D.; Meyer, W.P.; Perera, G.; Attapattu, S.; Kularatne, S.A.M.; Sheriff, M.H.R.; et al. (BMJ, 2000)
To describe the cardiac arrhythmias, electrolyte disturbances, and serum cardiac glycoside levels seen in patients presenting to hospital with acute yellow oleander (Thevetia peruviana) poisoning and to compare these with published reports of digitalis poisoning. DESIGN Case series. SETTING Medical wards of Anuradhapura District General Hospital, Sri Lanka, and coronary care unit of the Institute of Cardiology, National Hospital of Sri Lanka, Colombo, the national tertiary referral centre for cardiology. PATIENTS 351 patients with a history of oleander ingestion. MEASUREMENTS ECG and blood sample analysis on admission. RESULTS Most symptomatic patients had conduction defects affecting the sinus node, the atrioventricular (AV) node, or both. Patients showing cardiac arrhythmias that required transfer for specialised management had significantly higher mean serum cardiac glycoside and potassium but not magnesium concentrations. Although there was considerable overlap between groups, those with conduction defects affecting both sinus and AV nodes had significantly higher mean serum cardiac glycoside levels. CONCLUSIONS Most of these young previously healthy patients had conduction defects affecting the sinus or AV nodes. Relatively few had the atrial or ventricular tachyarrhythmias or ventricular ectopic beats that are typical of digoxin poisoning. Serious yellow oleander induced arrhythmias were associated with higher serum cardiac glycoside concentrations and hyperkalaemia but not with disturbances of magnesium.
Heart:2000; 83(3), 301-306p.
Keywords: oleander poisoning; arrhythmias; cardiac glycosides